Full-tab battery pole piece structure, full-tab battery roll core, full-tab battery
Patent Information
- Application Number
- CN202611167427.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-16
AI Technical Summary
1、增设金属遮光垫片:在极耳与隔膜之间额外增加薄金属垫片遮挡漏光,需要新增零件上料、精准定位工序,装配复杂度大幅提升,且垫片占用卷芯内部空间,降低电芯能量密度,同时引入新的金属异物风险;
[0014]As a preferred embodiment of the present invention, after the tabs of the negative electrode sheet are shaped, the inner surfaces of each negative electrode tab are stacked facing the center hole of the core to form a laser absorption surface, and the outer surfaces of each negative electrode tab are stacked outward to form a negative current collector welding surface; after the tabs of the positive electrode sheet are shaped, the inner surfaces of each positive electrode tab are stacked facing the center hole of the core to form a laser absorption surface, and the outer surfaces of each positive electrode tab are stacked outward to form a positive current collector welding surface.
Smart Images

Figure CN122930828A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of cylindrical lithium-ion battery manufacturing, specifically relating to a full-tab battery electrode structure, a full-tab battery core, and a full-tab battery. Background Technology
[0002] With the continuous improvement of the requirements for battery energy density and power performance in the new energy industry, large cylindrical all-tab batteries (such as 4680 and 4695 specifications) have become the mainstream technology route in the industry. The all-tab structure greatly increases the current-carrying area of the tabs by leaving the current collectors at the edges of the electrodes blank, cutting and stacking them, and then laser welding them to the current collector. This significantly reduces the internal resistance of the cell and improves the rate discharge capability and heat dissipation performance.
[0003] Currently, the industry commonly uses fiber laser penetration welding technology for current collectors and tabs: the laser enters from the outside of the current collector and melts the current collector and the blank tab metal in sequence to form a metallurgical bond. However, during mass production, due to the extremely thin thickness of the tab foil (negative electrode copper foil is usually 6~10μm, positive electrode aluminum foil is 10~15μm), and the presence of interlayer gaps and uneven thickness after dozens of tabs are stacked, some laser energy will penetrate the tab layer and dissipate to the inside of the core, directly irradiating the separator, causing the separator to melt and perforate, and thermal shrinkage wrinkles, ultimately leading to micro-short circuits in the battery cell, excessive self-discharge, cyclic gas expansion, and even thermal runaway safety hazards.
[0004] Regarding the aforementioned problem of laser light leakage damaging the diaphragm, existing mainstream solutions all have significant drawbacks: 1. Adding a metal light-shielding gasket: Adding an extra thin metal gasket between the tab and the diaphragm to block light leakage requires additional parts loading and precise positioning processes, which greatly increases the assembly complexity. In addition, the gasket occupies the internal space of the core, reduces the energy density of the cell, and introduces new risks of metal foreign objects. 2. Increase the length of the blank electrode tab: Increasing the distance between the welding position and the diaphragm to reduce the impact of light leakage directly leads to a significant increase in the amount of electrode tab material used, and the space of the core center hole is occupied, which does not conform to the design trend of high energy density. Summary of the Invention
[0005] To address the shortcomings described in the prior art, this invention provides a full-tab battery electrode structure, a full-tab battery core, and a full-tab battery. Without adding any additional parts, it efficiently absorbs the escaping laser energy penetrating the tabs, significantly reducing the defect rate of laser burns on the separator. Furthermore, it has strong process compatibility, does not significantly reduce electrical performance and energy density, and can be mass-produced at low cost.
[0006] The technical solution adopted in this invention is as follows: A full-tab battery electrode structure includes a full-tab electrode sheet with a tab region and a coating region. The tab region and the coating region are arranged adjacent to each other along the width direction of the full-tab electrode sheet. The tab region has several tabs, each tab having an outer surface and an inner surface. After the tabs are shaped, the outer surface serves as the welding surface for welding to the current collector, and the inner surface faces the center hole of the core. A ceramic light-absorbing layer is provided on the inner surface, completely covering the inner surface. The ceramic light-absorbing layer is directly coated on the tabs of the electrode sheet, providing in-situ light shielding without the need for additional parts. Moreover, after the tabs are shaped and flattened, when welding to the current collector, if the laser is incident from the current collector side, the stray laser light penetrating the tab substrate will directly hit the ceramic light-absorbing layer, which will absorb and block it, preventing it from reaching the separator. The ceramic light-absorbing layer absorbs excess laser energy without melting or perforating, thus not significantly reducing electrical performance and energy density.
[0007] In a preferred embodiment of the present invention, the thickness of the ceramic light-absorbing layer is 5~30μm. The absorption rate of the ceramic light-absorbing layer for laser light is 3-5 times that of copper foil and 4-6 times that of aluminum foil, and it can absorb more than 90% of the escaping laser energy that penetrates the tab.
[0008] In a preferred embodiment of the present invention, the ceramic light-absorbing layer is a ceramic coating made of any one or more composites of alumina, boehmite, and aluminum nitride. After absorbing excess laser energy, it will not melt or perforate, thus stably providing a light-shielding barrier function.
[0009] As a preferred embodiment of the present invention, the total tab electrode is a copper foil, and the coating area is coated with a negative electrode active material.
[0010] As a preferred embodiment of the present invention, the total tab electrode is an aluminum foil, and the coating area is coated with a positive active material.
[0011] This invention also provides a full-tab battery core, comprising a positive electrode, a negative electrode, and a separator, wherein the negative electrode has the aforementioned electrode structure. During battery assembly, regardless of whether the tabs are flattened or folded, laser leakage damaging the separator during current collector welding has always been a challenge for all lithium battery manufacturers. This invention directly coats the inner surface of the tabs with a ceramic light-absorbing layer, directly absorbing the dissipated laser energy.
[0012] As a preferred embodiment of the present invention, after the tabs of the negative electrode are shaped, the inner surfaces of each stack face towards the center hole of the core to form a laser absorption surface, and the outer surfaces of each stack face outward to form a current collector welding surface.
[0013] As a preferred embodiment of the present invention, both the positive electrode and the negative electrode are electrode structures as described above, with the positive electrode coating area coated with positive active material and the negative electrode coating area coated with negative active material.
[0014] As a preferred embodiment of the present invention, after the tabs of the negative electrode sheet are shaped, the inner surfaces of each negative electrode tab are stacked facing the center hole of the core to form a laser absorption surface, and the outer surfaces of each negative electrode tab are stacked outward to form a negative current collector welding surface; after the tabs of the positive electrode sheet are shaped, the inner surfaces of each positive electrode tab are stacked facing the center hole of the core to form a laser absorption surface, and the outer surfaces of each positive electrode tab are stacked outward to form a positive current collector welding surface.
[0015] The present invention also provides a multi-tab battery, comprising a core and a steel casing, wherein the core is the multi-tab battery core described above.
[0016] This invention directly coats the inner surface of the tab with a ceramic light-absorbing layer without adding any additional components. This achieves in-situ efficient absorption of the escaping laser energy that penetrates the tab, significantly reducing the defect rate of laser burns on the diaphragm. Moreover, it only requires adding a local coating station to the electrode coating process, without modifying subsequent core equipment such as winding, cutting, and welding. It is fully compatible with existing full-tab battery cell manufacturing processes. Compared with the metal light-shielding gasket solution, the material cost per battery cell is reduced by more than 60%, and there is no additional risk of foreign matter during assembly. Attached Figure Description
[0017] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0018] Figure 1 This is a side view of the electrode structure in Embodiment 1 of the present invention.
[0019] Figure 2 This is a front view of the electrode structure in Embodiment 1 of the present invention.
[0020] Figure 3 This is a diagram of the core structure wound using the electrode structure of Example 1. Detailed Implementation
[0023] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Example
[0024] A full-tab battery electrode structure includes a full-tab electrode 1. In this example, the full-tab electrode is made of copper foil with a thickness of 6-10 μm, and 8 μm is used in this embodiment. The full-tab electrode 1 has a tab region 11 and a coating region 12. The tab region 11 and the coating region 12 are arranged adjacent to each other along the width direction of the full-tab electrode 1. A boundary line 13 is formed at the position where the coating region 12 and the tab region 11 meet. The boundary line 13 is parallel to the length direction of the full-tab electrode 1. The coating region is coated with a negative electrode active material. In this embodiment, the negative electrode active material is graphite.
[0025] The tab region 11 has several tabs 2, which are formed by laser die-cutting the blank area of the full tab electrode sheet. Each tab 2 has an outer surface 21 and an inner surface 22. After the tab is shaped, the outer surface 21 serves as the welding surface for welding to the current collector, and the inner surface 22 faces the center hole of the core. A ceramic light-absorbing layer 3 is provided on the inner surface 22, completely covering the inner surface 22. The ceramic light-absorbing layer 3 is a ceramic coating made of any one or more composites of alumina, boehmite, and aluminum nitride. In this embodiment, an alumina ceramic light-absorbing layer is used, with a coating thickness of 5-30 μm, which can be 3 μm, 8 μm, 10 μm, 15 μm, 20 μm, 25 μm, or 30 μm; this embodiment uses 10 μm as an example.
[0026] A ceramic light-absorbing layer is directly coated on the tab of the electrode, providing in-situ light shielding without the need for additional parts. Moreover, after the tab is shaped and flattened, when welding it to the current collector, the laser beam that penetrates the tab substrate will directly hit the ceramic light-absorbing layer during welding from the current collector side. The laser beam will be absorbed and blocked by the ceramic light-absorbing layer, preventing it from reaching the diaphragm. The ceramic light-absorbing layer absorbs excess laser energy without melting or perforating, thus not significantly reducing electrical performance and energy density. Example
[0027] A full-tab battery electrode structure is provided. The full-tab electrode uses aluminum foil with a thickness of 10~15μm, and 12μm is used in this embodiment. The positive electrode active material coated in the coating layer is NCM811 material. A ceramic light-absorbing layer is coated on the inner surface of the positive tab. The rest is the same as in Example 1. Example
[0028] A type of all-tab battery core, such as Figure 3As shown, the structure includes a positive electrode, a negative electrode, and a separator. The separator is a 9μm PE substrate with a 2μm single-sided ceramic coating. The negative electrode is the same as the electrode structure in Example 1. The positive electrode uses a conventional positive electrode. After the tabs of the negative electrode are shaped, the inner surfaces 22 of each electrode are stacked facing the center hole of the core to form a laser absorbing surface. The outer surfaces are stacked outwards to form a current collector welding surface. When the laser is incident from the current collector side for welding, the escaping laser penetrating the tab substrate will directly hit the ceramic light-absorbing layer, where it is absorbed and blocked, preventing it from reaching the separator. The ceramic light-absorbing layer absorbs excess laser energy without melting or perforating, thus not significantly reducing electrical performance and energy density. Example
[0029] A full-tab battery, using the core and steel casing assembly method described in Example 3. Example
[0030] A multi-tab battery core includes a positive electrode, a negative electrode, and a separator. The separator is a 9μm PE substrate with a 2μm single-sided ceramic coating. The negative electrode has the electrode structure described in Example 1. The positive electrode uses the electrode structure described in Example 2.
[0031] After winding, the ceramic light-absorbing layers of the positive electrode and the negative electrode are all oriented towards the center hole of the core. After the positive and negative electrodes are oriented and flattened, they are laser welded to the positive and negative current collectors respectively. When the laser is incident from the current collector side during welding, the stray laser light penetrating the electrode substrate will directly hit the ceramic light-absorbing layer, which will be absorbed and blocked by the ceramic light-absorbing layer, preventing it from reaching the separator. The ceramic light-absorbing layer absorbs excess laser energy without melting or perforating, and there is no significant loss in electrical performance and energy density. The absorption rate of the ceramic light-absorbing layer to laser light is 3-5 times that of copper foil and 4-6 times that of aluminum foil, and it can absorb more than 90% of the stray laser energy penetrating the electrodes.
[0032] The effectiveness of the invention was verified by setting up experimental examples and comparative examples using the 4680 ternary lithium battery cell as an example.
[0033] Experimental example: Basic cell parameters: 4680 cylindrical cell, positive electrode uses NCM811 material, negative electrode uses artificial graphite, separator is 9μm PE substrate + 2μm single-sided ceramic coating; negative electrode current collector is 8μm copper foil, positive electrode current collector is 12μm aluminum foil.
[0034] Ceramic light-absorbing layer design: An alumina ceramic light-absorbing layer with a coating thickness of 10μm is set on the side of the negative electrode tab facing the center hole of the core; at the same time, an alumina ceramic light-absorbing layer with a coating thickness of 15μm is set on the side of the positive electrode tab facing the center hole of the core. After the electrode tabs are laser-die-cut and wound, the ceramic light-absorbing layers are uniformly oriented towards the central hole. Next, all the tabs are oriented and flattened. The wound core, after being oriented, flattened, and flattened, is then laser-welded to the current collector.
[0035] Actual test results: Mass production verification was conducted using 1800W laser power and 150mm / s welding speed. The diaphragm burn defect rate was 0.08%. The average welding pull force of the tabs was >120N, meeting the welding reliability requirements. The cell capacity retention rate after 1000 cycles at 1C was 89.2%, which was not significantly different from the conventional solution without ceramics (89.7%).
[0036] Comparative example: Using the exact same cell and welding parameters as the experimental example, but without a ceramic light-absorbing layer on the tabs; the measured diaphragm burn defect rate was 1.48%, which was much higher than that of the experimental example. Example
[0037] A full-tab battery includes a core and a steel casing, wherein the core is the full-tab battery core of Example 5.
[0038] In this specification, the terms "an embodiment," "example," "specific example," etc., refer to a specific feature, structure, material, or characteristic described in connection with that embodiment or example, which is included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0039] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A full-tab battery electrode structure, comprising a full-tab electrode (1), the full-tab electrode (1) having a tab region (11) and a coating region (12), the tab region (11) and the coating region (12) being arranged adjacent to each other along the width direction of the full-tab electrode (1), characterized in that: The tab area (11) has several tabs (2), each tab (2) has an outer surface (21) and an inner surface (22). After the tab is shaped, the outer surface (21) serves as the welding surface for welding with the collector plate, and the inner surface (22) faces the center hole of the core. A ceramic light-absorbing layer (3) is provided on the inner surface (22), and the ceramic light-absorbing layer (3) completely covers the inner surface (22).
2. The all-tab battery electrode structure according to claim 1, characterized in that: The thickness of the ceramic light-absorbing layer (3) is 5~30μm.
3. The all-tab battery electrode structure according to claim 1, characterized in that: The ceramic light-absorbing layer (3) is a ceramic coating made of any one or more of alumina, boehmite, and aluminum nitride.
4. The all-tab battery electrode structure according to any one of claims 1-3, characterized in that: The total electrode sheet is made of copper foil, and the coating area (12) is coated with negative electrode active material.
5. The all-tab battery electrode structure according to any one of claims 1-3, characterized in that: The total electrode sheet is made of aluminum foil, and the coating area (12) is coated with positive active material.
6. A multi-tab battery core, comprising a positive electrode, a negative electrode, and a separator, characterized in that: The negative electrode is the electrode structure described in claim 4.
7. The all-tab battery core according to claim 6, characterized in that: After the tabs of the negative electrode are shaped, the inner surfaces (22) are stacked facing the center hole of the core to form a laser absorption surface, and the outer surfaces are stacked facing outward to form a current collector welding surface.
8. The all-tab battery core according to claim 6, characterized in that: The positive electrode and the negative electrode are both electrode structures as described in any of claims 1-3, with the positive electrode coated with a positive active material and the negative electrode coated with a negative active material.
9. The all-tab battery core according to claim 8, characterized in that: After the tabs of the negative electrode are shaped, the inner surfaces (22) of each negative tab are stacked facing the center hole of the core to form a laser absorption surface, and the outer surfaces of each negative tab are stacked outward to form a negative current collector welding surface; after the tabs of the positive electrode are shaped, the inner surfaces (22) of each positive tab are stacked facing the center hole of the core to form a laser absorption surface, and the outer surfaces of each positive tab are stacked outward to form a positive current collector welding surface.
10. A multi-tab battery, comprising a winding core and a steel casing, characterized in that: The core is any one of the full-tab battery cores described in claims 6-9.